PEMANFAATAN BUAH NANGKA SEBAGAI PRODUK 3in1 SEBAGAI UPAYA MENINGKATKAN PEREKONOMIAN MASYARAKAT KECAMATAN GUNUNGPATI - Annisa, Arianti Nuur; Farida, Anna; Hakim, Luqman; Putra, Gita Permana; Mirnasari, Dhany (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
Gunungpati is one of subdistrict in Semarang city that is rich in natural sources, one of them is jackfruit which is produced up to 1.481,25 ton per years. Usually, the jackfruit is sold to the consumer directly without any processes. Hence, it is often rotten before sold. Proceed the jackfruit into syrup, jam and juice could increase its selling value. In other sides, most of people in Gunungpati work as labor with low income. It is expected that training may increase their skill and income. Survey showed that 77,7% of the people are eager to join the training and create a unit group as a media to empower the community in jackfruit production. The P-IRT (Home Industry License) was obtained to ensure the consumer on product safety hence, it supports continuity of the activity. The training not only result in skilled community but also increase their income up to 81,36% by selling the training product outcome.